ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KECENDERUNGAN KECURANGAN AKUNTANSI (STUDI PADA OPD KABUPATEN KUANTAN SINGINGI) - Julian Dini Astari; Raja Adri Satriawan Surya; Rheny Afriana Hanif (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to determine the effect of information asymmetry, rule enforcement, the effectiveness of internal control, unethical behavior, suitability of compensation , and the morality of apparatus towards the tendency of accounting fraud. The population in this study were employees in 26 organizations of Kuantan Singingi District. While the respondents consist of head of sub division of finance, Activity Technical Activity Officer (PPTK), and finance staff totaling 72 people. The method used in this study is purposive sampling. The data were analyzed using multiple regression method using SPSS version 21. The result of the research proves that (1) the information asymmetry does not influence the tendency of accounting fraud, (2) the rule enforcement influences the tendency of accounting fraud, (3) the effectiveness of internal control influence the tendency of accounting fraud, (4) unethical behavior has an effect on the tendency of accounting fraud, (5) suitability of compensation has no effect on the tendency of accounting fraud, (6) the morality of the apparatus has an effect on the tendency of accounting fraud. Based on the results of determination coefficient test or R 2 of 0.531 indicates that the tendency of accounting fraud influenced 53.1% by information asymteri, rule enforcement, effectiveness of internal control, unethical behavior, suitability of compensation, and morality of apparatus. While the remaining 46.9% influenced by other variablesKeywords : Information asymmetry, rule enforcement, the effectiveness of internal control, unethical behavior, suitability of compensation, morality of apparatus, tendency of accounting fraud